In the face of the sun [large type] - Bryce, Denny S. (Thorndike Press, a part of Gale, a Cengage Company, 2022)
"Los Angeles, 1928. An up-and-coming journalist, Daisy Washington anonymously chronicles fierce activism and behind-the-scenes Hollywood scandals to save her family from poverty. But power is also fueled by racism, greed, and betrayal. Chicago, 1968. For Frankie Saunders, fleeing across America is her only escape from an abusive husband. But her rescuer is her Aunt Daisy, still reeling from her own shattered past. Daisy will do whatever it takes to settle old scores and resolve the past. And Frankie will come up against hard choices in the face of unexpected passion. Both must come to grips with what they need, what they've left behind, and all that lies ahead."--Back cover